Testing the role of seed size in annual legume seedling performance under experimental autumn moisture conditions - Arellano, Gabriel; Peco, Begoña (Journal of Vegetation Science, 2012)
Question: Previous studies show that large-seeded species increase their abundance in Mediterranean annual grasslands in growing seasons with dry autumns. One possible explanation is that large-seeded species have larger seedlings, which provide an advantage under drier conditions. We address the following questions: is seed mass correlated with seedling survival in annual legumes? Is this correlation inﬂuenced by the watering regime? Can seedling growth characteristics explain the differential survival of small- and large-seeded species? Location: Annual Mediterranean grassland, Central Spain. Methods: An experiment was conducted with six grassland legume species of different seed sizes, subjected to six different watering regimes, monitoring survival and morphological variables (shoot and root growth) for 40 d. Results: Large seeds provide an advantage for seedling survival, but in extreme drought conditions, seedling survival in small-seeded species equals that of seedlings from large-seeded species. Seedlings from larger seeds are larger than those of small-seeded species, but have a lower root/shoot biomass ratio, leading to greater potential evapotranspiration, which could explain their loss of relative advantage under extreme droughts. Conclusion: The hypothesis that seedlings from large-seeded species survive better than small-seeded species under drought conditions was not supported. Germination behaviour seems to be a more plausible explanation for the increased abundance in the ﬁeld of large-seeded species in growing seasons with dry autumns.
Keywords: autumn drought; mediterranean therophytes; Pasture legumes; seed mass; seedling survival